A organização didática do ensino na educação infantil: implicações da teoria histórico-cultural - Lazaretti, Lucinéia Maria (Universidade Federal de São Carlos, 2013)
This present thesis is the result of a survey of exploratory bibliographical nature-explanatory notes and it aimed to analyze the possibilities of organizing didactic teaching in early childhood education, in the light of the Cultural-Historical Theory, based on pedagogical practices described in theses and dissertations produced in the period 1998-2010. The investigation led to the formulation of the following thesis: the didactic organization of teaching in early childhood education, grounded in theoretical-methodological bases of historical-Cultural Theory, can steer possibilities that promote children's learning and development from zero to six, directing the pedagogical practice of intentional and systematic way. The collection and selection of the material by the Capes portal, resulted in eleven dissertations and thesis, that described or analysed specific pedagogical practices in the everyday life of early childhood education. From this analysis, we articulated: there is an intentional and systematic education that target the pedagogical practices and, with it, the educational work is based in a fragmented teaching, in which the objectives-contents procedures appear off the context; There is no representative goals showing why to teach. This is due to a lack of to establish what to teach, how to teach and taking off the context; the teacher-student relationships and interactions are virtually absent and the mediation professor student knowledge is not representative and promoter of learning and development. This fragmented teaching reveals the fragility of didactic organization of teaching in early childhood education, where there is a break in the pedagogical practice from zero to six years: on the one hand, for children under three years, the educational process involves routines in care activities that prevail, fixed and rigid, with content geared to acquire habits and abilities restricted to daily life with goals of care, feed and maintain hygiene and adequate sleep; on the other hand, for children four to six years, isolated activities occur, with disconnected and fragmented subjects aimed to train and prepare for literacy, with exercises, instructional and training ready. These notes weaved some possibilities for forwarding the pedagogical practice in early childhood education. As conclusive synthesis, we argue that the didactic organization of teaching must have as the horizon full formation of the child and the child's education is takes ownership of the human and cultural forms this is the teacher's mediation that interferes in the zone of proximal development, challenging and encouraging the child to new learning. To do it, as representative of its educational work, we need to trace goals that promote maximum human potential crystallized in cultural heritage that needs to be appropriate in the form of content, enriched with, various, diverse and contextualized that make the pedagogical practice a space that represents the complex and elaborate human achievements, producing the cultural and human development in children.
The didactic organization of teaching in early childhood education: implications of historical-cultural theory
Keywords: Teoria histórico-cultural; Educação infantil; Didática; Ensino; Historical and cultural theory; Early childhood education; Didactics; Teaching; CIENCIAS HUMANAS::EDUCACAO